Electronic structure of LiOsO3: Electron energy-loss spectroscopy and first-principles study. (January 2021) - Wang, Y.R.; Wang, S.; Tao, H.L.; Cui, Y.; Liu, S.M.; He, M.; Song, B.; Zhang, Z.H.
Abstract: Electronic structure of LiOsO3 were investigated by using first-principle calculations and electron energy loss spectroscopy (EELS). According to the calculated densities of states, the interband transitions from valence band (VB) to conduction band (CB) to the low energy loss spectrum were assigned. The hybridization of O 2p with Os 5d was critical to the coexistence of metal and ferroelectricity in LiOsO3 . From the simulation of the energy loss near-edge structure (ELNES), the fine structure of O K-edge was in good agreement with the experimental spectrum, while the core hole effect and spin-orbital coupling had little effect on the spectra. Highlights: Electronic structure of LiOsO3 were investigated by using first-principle calculations and EELS. The hybridization of O 2p with Os 5d was critical to the coexistence of metal and ferroelectricity. According to the EELS, the orbital transition and bond hybridization are given. The results would provide a theoretical basis for the further study on LiOsO3 in the future.